STRIVING FOR DIABETES SELF-CARE MANAGEMENT IN THE OLDER PEOPLE BASED ON SELF-DETERMINATION THEORY - Vitaliati, Trisna; Angelia Silvanasari, Irwina; Maurida, Nurul; Ali Basri, Achmad (Universitas Airlangga, 2024)
Introduction: Older people with diabetes mellitus need disease management through self-management which is quite complex because the disease will have an impact on their health condition both physically and psychologically. Based on Self Determination Theory, motivation is important component in improving psychological health and treatment effectiveness of patients with diabetes mellitus. The purpose of this community service is to strive for diabetes self-care management so that blood sugar levels can be controlled reduce the risk of complications and achieve a prosperous psychological condition. Methods: The method of implementing this community service is in the form of health education, early screening, diabetes gymnastics, and family assistance in carrying out family healthcare functions. This community service was carried out at Jenggawah Public Health Center in March 2023. The participants of this community service activity are older people with diabetes mellitus. Results: There is an increase in the motivation of older people to carry out self-care activities, and the older people and families can also practice diabetes gymnastics by what has been taught. Conclusion: With optimal management behavior of diabetes mellitus in older people, the psychological aspects of the elderly with Diabetes Mellitus will improve so that further complications of this disease can be prevented.